Sundanese Muslim Community's Understanding of Sufism: A Phenomenological Approach - Yana Sutiana; Afif Muhammad; Dadang Kahmad; Muhtar Solihin (Jurnal Iman dan Spiritualitas, 2022)
This study examined the Sundanese ethnic understanding of Sufism and its implications in social life. The research approach is a phenomenological study in the scientific paradigm of religious studies, which is descriptive qualitative empirical and uses grounded research methods. The research data comes from Sundanese Muslim leaders, cultural figures, and academic figures. This research finds that according to Islamic Sundanese figures, ethnic Sufism is a development of understanding of every society's religious thoughts, attitudes, and practices in dealing with the problems of modernity. Also, ethnic Sufism is a form of penetration of Sundanese ethnic local wisdom into religion. This study also suggests that the elements of Sufism influence the esoteric understanding of Sundanese Muslim religion based on the understanding of Sufism from Sundanese leaders, whether from religious leaders, cultural leaders, or academic figures. Sundanese ethnic Sufism is still preserved in the traditions of modern Sundanese society, for example, first, in the practice of the ritual traditions of the South Coast Sundanese ethnicity. This coastal area is very thick with the early process of the entry of Islam.